Od pamięci biodziedzicznej do postpamięci - Szostek, Teresa; Sendyka, Roma; Nycz, Ryszard (Nowa Humanistyka, 2013)
This volume comprises texts created on the basis of three-fold meetings: the first kind were constituted by lectures led by invited guests, representing various fields and areas of research, which, in some necessary simplification, can be divided into historiography (Ewa Domańska), philosophy (Agata Bielik-Robson), literary and memory studies (Michael Rothberg), and philosophy of literature (Michał Paweł Markowski). The lectures were accompanied by workshops, whose leaders present their texts in the second part of the work, and the third part is made up of notes from panel talks. As per the nature of these types of sessions, they present themselves as highly intense (various meetings from morning until evening), as well as showing the unavoidable variety in outlooks, which is one of the major advantages of such events. Another advantage is a slightly more 'personalist' encounter, not so much with text, but with the figure of an author, and thus also with the personality of a researcher. What became the idea bringing all these activities together was memory, understood and treated in very different ways. The variety of starting points and views on the forms and places of the functioning of memory then transformed itself into an abundance of experiences of the 'originators' and the richness of feelings (also of those imprinting themselves in memory) of the 'receivers'.